Increasing fish production through adoption of improved technologies in Ogun State, Nigeria - Segun, Ashley-Dejo Samuel; Temitope, Oyetunji Opeyemi; Okanlawon, Sule Shakiru; Abiola, Durojaiye Fadilat; Teslim, Ojetayo Asaje; Ruth, Ojinni Temitope (Aceh Journal of Animal Science, 2024)
Technology is one of the crucial factor influences the aquaculture production; hence it is essential to encouragefish farmers to embrace modern methods of fish production by utilizing improved fisheries and aquaculture technologies This study assessed the factors that influence adoption of improved fish production technologies in Ogun State, Nigeria. The study adopted survey design and data were collected through structured questionnaire administered to 150 fish farmers by adopting multistage sampling procedure. It was observed that majority of the respondents were male, married, literate and made use of family labor. The study also found that fish enclosure technologies, neutralizers/fertilizers, and fish stock selectivity/harvesting gear systems were distributed among fish farmers in the study area, with earthen fish ponds being the most widely adopted technology. Furthermore, the study revealed that fish farmers generally had positive attitudes towards the use of improved technologies. The study also found that high production costs were the most significant constraint to the adoption of improved technologies, followed by inadequate contact with extension agents and non-availability of input. The study conclude that the adoption of improved fish production technologies could increase fish production in Ogun State, Nigeria, but there is a need for interventions to address the constraints hindering the adoption of improved fisheries technologies in the study area.